Repatriation account
1940-03-27 038-0046-001 REPATRIATION ACCOUNT 12th Dec. 1939. Southern Railway. 365:17:11 Food & incidental expenses of journey 48:13: 3 414:11: 2 19th " " Southern Railway. 470: 4: 5 Food & incidental expenses of journey. 55: 5: 9 525:10: 2 16th Jan.1940 Southern Railway 206 : 3 : 2 Food & incidental expenses of journey. 47: 7: 7 253:10: 9 3rd Feb. " Southern Railway. 132: 2:11 Food & incidental expense of journey. 40: 2: 3 172: 5: 2 1365: 17: 3 estimated cost of travel in England from Centres to London. 170: 0: 0 £1535:17: 3 Balance at Bank of Repatriation Fund. £146: 3: 2 The above balance is not sufficient to cover the Railway Companies' charges for travel in England. estimated at £170. M Holland. 27th Mar. 1940. 292/946/38/46(I)